Analysis of the factors influencing red clover (Trifolium pratense L., Fabaceae) isoflavone content - Sazdanić , Darija; Mikulić, Mira; Kladar, Nebojša; Hogervorst, Jelena; Atanacković Krstonošić, Milica (Biologia Serbica, 2019)
This paper summarizes published literature concerning different factors that could affect the content and composition of isoflavones in red clover (Trifolium pratense L., Fabaceae). Influence of genotype, plant part, geographic origin, ontogeny and storage conditions of raw material are discussed. Statistical analysis of available data on the profile of isoflavones in red clover suggest that, in general, samples are grouped according to country of origin, indicating the importance of climate conditions. An increase in biosynthesis of isoflavones as a response to different abiotic factors is also considered. Knowledge about these factors is of great practical importance, since red clover is a medicinal plant widely used for production of dietary supplements, and producers aim to breed cultivars with high isoflavone concentrations.